Symbolism of Natural Imagery in Prose of Russian Émigré Writers (E. Yu. Skobtsova, N. D. Gorodetskaya, V. A. Nikiforov-Volgin) - V. T. Zakharova; I. S. Kudryavtseva (Научный диалог, 2024)
This study explores the issue of symbolization of natural imagery in an ontological, existential sense through the works of authors belonging to the first wave of Russian literary emigration. It is noted that in E. Yu. Skobtsova’s novel “Russian Plain”, a mythologized image of spiritualized space is created, encompassing an expressively colored image of the motherland, calling on children to respond to universal pain. In the autobiographical prose of N. D. Gorodetskaya, past and present converge in a unified sense of gratitude: the gracious, invaluable past seems to merge into the present, giving it integrity and significance, with the native surrounding world in the past becoming the writer’s main life support, a great ontological value. V. A. Nikiforov-Volgin’s works reveal a typologically similar mythologization of space in an original individual-authorial perception, accentuating the motif of the sacredness of the latter, expressing the drama of the years of adversity; with N. D. Gorodetskaya, the writer is united by a perception of the harmony of the native surrounding world with a child’s soul. The analysis conducted convinces that the artistic thinking of E. Yu. Skobtsova, N. D. Gorodetskaya, V. A. Nikiforov-Volgin developed in a typological stream of neorealistic artistic consciousness characterized by a multifaceted synthesis of various artistic elements.